On the -Bernstein Polynomials of Unbounded Functions with - Sofiya Ostrovska; Ahmet Yaşar Özban (Abstract and Applied Analysis)
The aim of this paper is to present new results related to the -Bernstein polynomials of unbounded functions in the case and to illustrate those results using numerical examples. As a model, the behavior of polynomials is examined both theoretically and numerically in detail for functions on satisfying as , where and are real numbers.